Size Perception Bias and Reach-to-Grasp Kinematics: An Exploratory Study on the Virtual Hand With a Consumer Immersive Virtual-Reality Device - Itaguchi, Yoshihiro (Frontiers in Virtual Reality, 2021)
While studies have increasingly used virtual hands and objects in virtual environments to investigate various processes of psychological phenomena, conflicting findings have been reported even at the most basic level of perception and action. To reconcile this situation, the present study aimed (1) to assess biases in size perception of a virtual hand using a strict psychophysical method and (2) to provide firm and conclusive evidence of the kinematic characteristics of reach-to-grasp movements with various virtual effectors (whole hand or fingertips only, with or without tactile feedback of a target object). Experiments were conducted using a consumer immersive virtual reality device. In a size judgment task, participants judged whether a presented virtual hand or an everyday object was larger than the remembered size. The results showed the same amplitude of underestimation (approximately 5%) for the virtual hand and the object, and no influence of object location, visuo-proprioceptive congruency, or short-term experience of controlling the virtual hand. Furthermore, there was a moderate positive correlation between actual hand size and perception bias. Analyses of reach-to-grasp movements revealed longer movement times and larger maximum grip aperture (MGA) for a virtual, as opposed to a physical, environment, but the MGA did not change when grasping was performed without tactile feedback. The MGA appeared earlier in the time course of grasping movements in all virtual reality conditions, regardless of the type of virtual effector. These findings confirm and corroborate previous evidence and may contribute to the field of virtual hand interfaces for interactions with virtual worlds.